The global costs of schizophrenia. - Knapp, M; Mangalore, R; Simon, J (2004)
Schizophrenia is a chronic disease associated with a significant and long-lasting health, social, and financial burden, not only for patients but also for families, other caregivers, and the wider society. Many national and local studies have sought to estimate the societal burden of the illness--or some components of it--in monetary terms. Findings vary. We systematically reviewed the literature to locate all existing international estimates to date. Sixty-two relevant studies were found and summarized. Within- and between-country differences were analyzed descriptively. Despite the wide diversity of data sets and methods applied, all cost-of-illness estimates highlight the heavy societal burden of schizophrenia. Such information helps us to understand the health, health care, economic, and policy importance of schizophrenia, and to better interpret and explain the large within- and across-country differences that exist.